BAG ATO-ASPECT AND MODERNIZATION OF EDUCATIONAL OF THE EDUCATIONAL PROCESS IN FOREIGN LANGUAGE CLASSES IN FRAMEWORK OF PERSONALITY-ORIENTED PARADIGM IN TECHNICAL HIGH SCHOOL (Pedagogy of Higher and Secondary Education, 2008)
The main aspects of educational-upbringing process in the university within personality orientedparadigm are described in détails in the articleю
Keywords: Bologna process; educational policy; personality-oriented paradigm; experience; verbal environment; self-détermination; behavioural science; responsibility; priorities in communication; art of teaching